Cohesive software measurement planning framework using ISO standards: a case study from logistics service sector. Issue 7 (13th April 2012) - Kurtel, Kaan; Ozemre, Murat
SUMMARY The objective of this paper is to present a cohesive measurement planning framework based on our successful practices during the implementation of a measurement process in a leading custom software development company in the logistics service sector in Turkey. The framework established is the result of the process of understanding how to plan software maintenance measurement that conforms to existing ISO/IEC standards, including ISO/IEC 9126, ISO/IEC 14598, and ISO/IEC 15939, and also combining the theoretical aspects of these standards with the realities of the software maintenance process in order to develop a software application. The main contributions of the article include the presentation of a practical solution in ISO‐based software measurement methodology and the elimination of the unnecessary and redundant ISO/IEC 9126 quality characteristics or sub‐characteristics for the purpose of application of quality model to the company, and identification of the suitable base and derived measurement sets for satisfying the company's information needs. Copyright © 2012 John Wiley & Sons, Ltd.